PENDAMPINGAN DALAM MENINGKATKAN KEMAMPUAN STATISTIK MAHASISWA DENGAN SOFTWARE R - Alamsyah Alamsyah; Dadang Hikmah Purnama; Gita Isnayawulan; Muhammad Izzudin; Erlisa Saraswati (As-Sidanah, 2022)
This article aims to describe the process and results of community service activities that seek to improve the knowledge and skills of IAIQ (Institute of Islamic Religion and Quran) al-Ittifaqiah Indralaya students in processing statistical data with R software. The service activity was carried out for two days. The first day adopted the tutorial lecture method, which included discussion, questions, and answers. While the second day focused on a data processing practicum with R, The results of the pre-test showed that the average knowledge of the target group on statistical data processing with R was only 10.41 points. After the training, the average score of the participants increased to 21.85 points. This service activity was statistically proven to increase the knowledge and skills of the participants; t (40) = 15.2719, p 0.001. The existence of this community is expected to become an arena for learning and sharing information about R. In addition, Sriwijaya University needs to continue financing the introduction of R software to the younger generation in the Ogan Ilir District, especially among students. Because mastering R is a form of digital competence for the younger generation of Indonesia who will work in the Revolution 5.0 era.